2021
DOI: 10.1111/jfbc.13577
|View full text |Cite
|
Sign up to set email alerts
|

Propolis ameliorates restenosis in hypercholesterolemia rabbits with carotid balloon injury by inhibiting lipid accumulation, oxidative stress, and TLR4/NF‐κB pathway

Abstract: Neointima formation and atherosclerosis are the main complications after the endovascular intervention and vascular surgery, and there are no effective drugs.Propolis is a kind of resin substance produced by honeybees and has numerous health-beneficial effects. In this study, we evaluated the effects of propolis (125 and 250 mg•kg -1 •day -1 , 6 weeks) on carotid restenosis in hypercholesterolemia rabbits.Propolis significantly ameliorated the degree of carotid restenosis, inhibited neointima hyperplasia, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Similar result was also observed in the hypercholesterolemia rabbits. Propolis consumption reduced the level of C-reactive protein, IL-6, and TNF-α, and inhibited the expression of CD68, TLR4, NF-κB p65, MMP-9, and TNF-α in the carotid arteries [ 73 ]. Further, Cardinault [ 74 ] found that propolis induced the expression of Nrf2-target genes in adipocytes, transactivated Nrf2 response element and the Nrf2 DNA-binding in mice [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar result was also observed in the hypercholesterolemia rabbits. Propolis consumption reduced the level of C-reactive protein, IL-6, and TNF-α, and inhibited the expression of CD68, TLR4, NF-κB p65, MMP-9, and TNF-α in the carotid arteries [ 73 ]. Further, Cardinault [ 74 ] found that propolis induced the expression of Nrf2-target genes in adipocytes, transactivated Nrf2 response element and the Nrf2 DNA-binding in mice [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…STAT1 [493], JAK2 [494], NOTCH2 [495], PDGFC (platelet derived growth factor C) [143], RASA1 [262], TLR6 [496], NOD2 [482], JMJD1C [483], CAVIN1 [485], POU2F1 [497], RPS5 [498] and LGALS3 [499] are involved in the regulation of cardiac fibrosis. TLR4 [500], ABCA1 [501], CCR2 [502], LDLR (low density lipoprotein receptor) [503], SIRT1 [504] and NOD2 [505] might crucially contribute to the development of hypercholesterolemia. ABCA1 [506], TLR5 [507], PTGS2 [508], TGFA (transforming growth factor alpha) [509], PDK4 [510], JAK2 [511], TLR2 [512], NEK7 [513], CCR1 [514], BACH1 [515], NCOA4 [195], LATS2 [516], PELI1 [517], EGR1 [518], CYBB (cytochrome b-245 beta chain) [519], MEFV (MEFV innate immuity regulator, pyrin) [520], CLEC4E [521], GCLC (glutamate-cysteine ligase catalytic subunit) [522], KLF3 [523], TP53INP1 [524], ITGB1 [525], IRF9 [526], PHLPP1 [527], NOD2 [528], ACSL4 [529], FGL2 [530], PF4 [531], VEGFB (vascular endothelial growth factor B) [532], CCR7 [533], IGFBP4 [534], TRPM4 [535], BAG1 [536], LGALS3 [537] and ATAD3A [538] could induce ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attenuating oxidative stress may potentially decelerate the progression of atherosclerotic plaque formation ( 22 ). Ji et al ( 23 ) revealed that propolis ameliorated restenosis in hypercholesterolemia rabbits with carotid balloon injury by inhibiting lipid accumulation, oxidative stress and the Toll-like receptor 4/NF-κB signaling pathway. Zhang et al ( 24 ) reported that quercetin is a potential therapeutic agent ameliorating atherosclerotic pathophysiology in rat carotid arteries by inhibiting oxidative stress and inflammatory response, the mechanism of which involved modulating the AMP-activated protein kinase/sirtuin 1/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%